1975
DOI: 10.1007/bf00581832
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic characteristics of heart-rate responses to sine-function work-load patterns in man

Abstract: Dynamic characteristics of heart rate in response to sinusoidal variations of work load were analysed in 8 male and 3 female untrained students exercising in a sitting position on a bicycle ergometer. The mean work load was 90 watt in men and 60 watt in women, the amplitudes being 50 and 30 watt respectively. Nine different frequencies were used, the periods varying from 0.5 to 15.0 min. By means of harmonic analysis, the fundamental components in the response of the heart rate have been shown to prevail over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…We theorize that resonant properties underlie CVS function variability (Vaschillo, Zingerman, Konstantinov, & Menitsky, 1983;Vaschillo et al, 2002). Rhythmical physical loading (Wigertz, 1971;Tiedt, Wohlgemuth, & Wohlgemuth, 1975), gravitation tilting (Hamilton, Lindan, & Reswick, 1969), rhythmical thermal stimulation (Lindqvist, 1990), rhythmical presentation of emotional pictures , and paced respiration all elicit high-amplitude oscillations in cardiovascular functions at resonant frequencies. HR resonance in the CVS at a frequency of ∼ 0.1 Hz has been discussed for more than 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…We theorize that resonant properties underlie CVS function variability (Vaschillo, Zingerman, Konstantinov, & Menitsky, 1983;Vaschillo et al, 2002). Rhythmical physical loading (Wigertz, 1971;Tiedt, Wohlgemuth, & Wohlgemuth, 1975), gravitation tilting (Hamilton, Lindan, & Reswick, 1969), rhythmical thermal stimulation (Lindqvist, 1990), rhythmical presentation of emotional pictures , and paced respiration all elicit high-amplitude oscillations in cardiovascular functions at resonant frequencies. HR resonance in the CVS at a frequency of ∼ 0.1 Hz has been discussed for more than 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that high‐amplitude 0.1 Hz HR oscillations were caused by emotional picture cue stimulation at a rate of 0.1 Hz (5 s picture on, 5 s picture off) (Vaschillo et al, 2008). Effects of rhythmical physical load on CVS functions also have been investigated (Lehrer, Vaschillo, Trost, & France, 2009; Tiedt, Wohlgemuth, & Wohlgemuth, 1975; Wigertz, 1971). The most comprehensive study (Wigertz, 1971) found that rhythmical physical loads varying from 250 to 1050 kpm/min at discrete frequencies in a range of 0.022–0.001 Hz (period range 0.75–16.67 min) caused sine‐wave oscillations in BP, HR, VT, partial O 2 pressure in blood (PO 2 ), respiration rate, and tidal volume.…”
Section: Rhythmical Stimulation Of the Cvs May Elicit Oscillation In mentioning
confidence: 99%
“…It has recently been reported that the dynamic response to HR and Po, to changes in relative or absolute work load is closely correlated with VO,,,, in untrained men, in children and in athletes (Cooper et al 1985, Powers et al 1985, EBfeld et al 1987, Grucza et al 1989, Zhang et al 1991. I n addition, Tiedt et al (1975) reported that in the sinusoidal exercise test subjects with a higher physical work capacity a t a heart rate of 170 b.p.m. (PWC,,,) were characterized by a faster HR response.…”
mentioning
confidence: 99%